Use of traditional and complementary medicine among Norwegian cancer patients in the seventh survey of the Tromsø study - Kristoffersen, Agnete Egilsdatter; Stub, Trine; Broderstad, Ann Ragnhild; Hansen, Anne Helen (BMC Complementary and Alternative Medicine, 2019)
Background : Traditional and complementary medicine (T&CM) is commonly used by cancer patients in Northern Norway, in particular spiritual forms like traditional healing. T&CM is mainly used complementary to conventional cancer treatment and is rarely discussed with conventional health care providers, increasing the risk of negative interaction with conventional cancer care. The aim of this study was to investigate the use of T&CM among cancer patients in Tromsø, and to investigate the differences in T&CM use between people living with cancer, people with cancer previously, and people without a history of cancer. Method : Data was drawn from the seventh survey of the Tromsø study conducted in 2015–2016. All inhabitants of Tromsø aged 40 and above were invited to participate (n = 32,591) of whom n = 21,083 accepted the invitation (response rate 65%). Data was collected thorough three self-administered questionnaires and a comprehensive clinical examination. Pearson chi-square tests, Fisher exact tests and one-way ANOVA tests were used to describe differences between the groups while binary logistic regressions were used for adjusted values. Results : Eight percent of the participants ( n = 1636) reported to have ( n = 404) or have had ( n = 1232) cancer. Of the participants with cancer at present 33.4% reported use of T&CM within the last year, 13.6% had consulted a T&CM provider, 17.9% had used herbal medicine/natural remedies and 6.4% had practiced self-help techniques. The participants with cancer at present were more likely to have visited a T&CM provider than participants with cancer previously (13.6% vs. 8.7%, p = 0.020). Among the participants with cancer at present, 6.4% reported to have consulted a TM provider, 5.8% had consulted an acupuncturist, while 4.7% had consulted other CM providers. Women were significantly more likely than men to have used acupuncture and self-help techniques. No significant gender differences were found regarding visits to other CM providers, TM ...